Impact of conjugation on the rheological properties of pulse protein-polysaccharide mixtures - Pervin Ari Akin; Iris J. Joye; Maria G. Corradini; Matthew Nosworthy; Yolanda Brummer; Phillip Lee Wing; Steve W. Cui (Food Hydrocolloids, 2026)

Seasonal variation in the use of food resources by sperm whales in a submarine canyon - Marta Guerra; Amandine Sabadel; William Rayment; Steve Dawson; Lucy Wing (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Evidence of a range expansion in sunfish from 47 years of coastal sightings - Olga Lyashevska; Deirdre Brophy; Steve Wing; David G. Johns; Damien Haberlin; Thomas K. Doyle (Marine Biology, 2022)
Almost nothing is known about the historical abundance of the ocean sunfish. Yet as an ecologically and functionally important taxa, understanding changes in abundance may be a useful indicator of how our seas are responding to anthropogenic changes including overfishing and climate change. Within this context, sightings from a coastal bird observatory (51.26 $$^°$$ ∘ N, 9.30 $$^°$$ ∘ W) over a 47 year period (from April to October 1971–2017) provided the first long-term index of sunfish abundance. Using a general linear mixed effect model with a hurdle to deal with imperfect detectability and to model trends, a higher probability of detecting sunfish was found in the 1990s and 2000s. Continuous Plankton Recorder (CPR) phytoplankton color indices and the annual mean position of the 13 $$^{° }$$ ∘ C sea surface isotherm were significantly correlated with the probability of detecting sunfish. An increase in siphonophore abundance (as measured by the CPR) was also documented. However, this increase occurred 10–15 years after the sunfish increase and was not significantly correlated with sunfish abundance. Our results suggest that the observed increase in sunfish sightings is evidence of a range expansion because it was significantly correlated with the mean position of the 13 $$^{° }$$ ∘ C isotherm which moved northwards by over 200 km. Furthermore, the observed increase in sunfish occured 10 years before sunfish sightings are documented in Icelandic and Norwegian waters, and was concurrent with well-known range expansions for other fish species during the 1990s. This study demonstrates how sustained citizen science projects can provide unique insights on the historical abundance of this enigmatic species.